Genetic Polymorphism of 5,10-MTHFR Reductase Gene in Offspring of Patients with Myocardial Infarction - Margaglione, Maurizio; Colaizzo, Donatella; Cappucci, Giuseppe; del Popolo, Annamaria; Vecchione, Gennaro; Grandone, Elvira; Di Minno, Giovanni (Thrombosis and Haemostasis, 1999)
A family history of myocardial infarction is a major determinant of ischemic disease. A C->T677 polymorphism in the methylenetetrahydrofolate reductase (MTHFR) gene has been identified as a cause of mild hyperhomocysteinemia, a risk factor for arterial thrombosis. We have investigated the relationship between the MTHFR TT genotype and a family history of myocardial infarction in a cohort of 982 apparently healthy individuals. Subjects whose first-degree relatives suffered from a myocardial infarction, showed raised median age (p <0.001), total cholesterol (p <0.001) and plasma fibrinogen (p = 0.023) and a higher than normal frequency of C-reactive protein levels >0.33 mg/dl (p = 0.012). Moreover, when compared to subjects without such family history, a higher number of homozygotes for the T allele of the MTHFR gene (p = 0.027), and of the 4G allele of the plasminogen activator inhibitor-1 gene (p = 0.002) was found in the subsetting of the offspring of patients with myocardial infarction. In a multiple logistic regression analysis, age (OR 1.02 [95%-CI: 1.00-1.05]), total cholesterol (OR 1.40 [95%-CI: 1.14-1.71]), C-reactive protein levels >0.33 mg/l (OR: 1.87 [95%-CI: 1.10-3.20]), plasminogen activator inhibitor-1 4G/4G (OR: 1.84 [95%-CI: 1.27-2.66]), and MTHFR TT genotype (OR 1.62 [95%-CI: 1.08-2.42]), were all associated with a family history of myocardial infarction. Thus, the MTHFR TT genotype independently accounts for the risk of a family history for myocardial infarction in the present setting.
Keywords: Myocardial infarction; risk factors; genes; methylenetetrahydrofo-late reductase